2013
DOI: 10.5586/aa.2013.031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growth regulator Kelpak SL on the formation of aboveground biomass of Festulolium braunii (K. Richt.) A. Camus

Abstract: A study on the cultivation of Festulolium braunii cv. 'Felopa' was carried out using polyurethane rings with a diameter of 36 cm and a height of 40 cm, which were sunk into the ground to a depth of 30 cm and filled with soil material. In this experiment, Kelpak SL was used as a bioregulator. It consists of natural plant hormones such as auxins (11 mg in dm3) and cytokinins (0.03 mg in dm3). The experimental factors were as follows: A1-control; A2 – 20% solution of the growth regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 5 publications
2
9
0
Order By: Relevance
“…Cytokinins have an impact on the enhancement and growth of the plant root system [106,107]. Therefore, the results obtained are not surprising; they only confirm the yield-enhancing role of PGPEm [108][109][110]. The conducted research study has shown that PGPEm protects potato tubers against silver scurf better than MSADs (Figure 4).…”
Section: Discussionmentioning
confidence: 98%
“…Cytokinins have an impact on the enhancement and growth of the plant root system [106,107]. Therefore, the results obtained are not surprising; they only confirm the yield-enhancing role of PGPEm [108][109][110]. The conducted research study has shown that PGPEm protects potato tubers against silver scurf better than MSADs (Figure 4).…”
Section: Discussionmentioning
confidence: 98%
“…ProbioHumus had the most marked effect on the growth of oats, with a 22% increase in plant height compared to the control plants, and an average increase of 14% in wheat treated with ProbioHumus. According to scientific data, increased plant growth with non-microbial inoculants was in some cases associated with increased chlorophyll and carotenoid content and improved plant nutrient status [ 41 ]. It has been reported in the literature that Kelpak treatment of seaweed resulted in a 10% increase in chlorophyll content compared to control plants [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kelpak is the brand name of a biostimulant containing Ecklonia maxima extract. In the work of Sosnowski [41], Kelpak extract from Ecklonia maxima increased biomass yield, number of shoots and leaf length in Festulolium braunii. The greenness index of leaves in plots sprayed with the highest concentration (60%) of Ecklonia maxima extract Kelpak was characterized by significantly higher SPAD values.…”
Section: Seaweed Extractsmentioning
confidence: 98%
“…Humic and fulvic acids Festulolium braunii K. Richt. A. Camus increased hemicellulose content, decreased non-structural carbohydrates content [38] Humic and fulvic acids annual bluegrass increased internalization of bacteria into root cells, promoted vertical root growth, enhanced root hair elongation, potential rhizophagy-and endophytism-enhancing properties [32] Humic and fulvic acids rough bluegrass no significant effect on growth or N and P uptake [36] Humic and fulvic acids orchard grass (Dactylis glomerata L.) altered content of proteins, carbohydrates, cellulose, hemicellulose, lignin and non-structural carbohydrates [35,[60][61][62][63] Humic and fulvic acids perennial ryegrass (Lolium perenne L.) enhanced dry matter digestibility and reduced content of structural carbohydrates and lignin [45] Seaweed extracts perennial ryegrass (Lolium perenne L.) improved dry matter digestibility and reduced content of structural carbohydrates and lignin [45] Seaweed extracts annual ryegrass (Lolium multiflorum L.) improved yields [35] Seaweed extracts Festulolium Braunii increased biomass yield, enhanced number of shoots, longer leaf length, higher SPAD values [41] Seaweed extracts orchard grass altered content of proteins, carbohydrates, cellulose, hemicellulose, lignin and non-structural carbohydrates [35,[60][61][62][63] Effective microorganisms perennial ryegrass reduced soil microorganisms, no effect on plant growth, improved chemical composition (increased CP, P, chlorophyll; decreased CF, K, Ca) [44] Effective microorganisms annual ryegrass expanded carbohydrate-to-protein ratio, increased crude ash content, improved digestibility, increased dry matter yield, natural yield increase [64][65][66][67] Effective microorganisms orchard grass and perennial ryegrass increased dry matter yield, crude protein content and soluble carbohydrates, increased cellulose and hemicellulose content [37,39] Effective microorganisms various grasses no significant effect on nutritional value (NDF, ADF, dry matter intake, digestibility) [68] Table 3. Cont.…”
Section: Biostimulant Plant Species Effect Referencesmentioning
confidence: 99%